Influence of simulated gastrointestinal conditions on particle-induced cytotoxicity and interleukin-8 regulation in differentiated and undifferentiated Caco-2 cells. Issue 4 (June 2013) - Gerloff, Kirsten; Pereira, Dora I.A.; Faria, Nuno; Boots, Agnes W.; Kolling, Julia; Förster, Irmgard; Albrecht, Catrin; Powell, Jonathan J.; Schins, Roel P.F.
Abstract Novel aspects of engineered nanoparticles offer many advantages for optimising food products and packaging. However, their potential hazards in the gastrointestinal tract require further investigation. We evaluated the toxic and inflammatory potential of two types of particles that might become increasingly relevant to the food industry, namely SiO2 and ZnO. The materials were characterised for their morphology, oxidant generation and hydrodynamic behaviour. Cytotoxicity and interleukin-8 mRNA and protein expression were evaluated in human intestinal Caco-2 cells. Particle pretreatment under simulated gastric and intestinal pH conditions resulted in reduced acellular ROS formation but did not influence cytotoxicity (WST-1 assay) or IL-8 expression. However, the differentiation status of the cells markedly determined the cytotoxic potency of the particles. Further research is needed to determine the in vivo relevance of our current observations regarding the role of particle aggregation and the stage of intestinal epithelial cell differentiation in determining the hazards of ingested particles.